ENERGY-ENTROPIC VALUE OF ORGANIZATION’S RESOURCES - Alla Bondar (Сучасний стан наукових досліджень та технологій в промисловості)
The subject of the study are approaches and methods for determining the energy and entropy values of the organization’s resources. The purpose of this study is to develop a concept and appropriate mathematical tools for determining and analyzing the dynamics of the energy-entropic value of the organization’s resources. To achieve this goal, it is necessary to perform the following tasks: determine the expression of energy entropy, formulate a model of the organization’s energy turnover, develop a system of indicators to determine the entropy value of the organization’s resources. The following methods are used: system analysis, probability theory, energy-entropy theory. Results. As a result of the study, it was found that in the process of the organization’s activity a cycle of protoenergy and energy occurs: energy – protoenergy (resources) - protoenergy (product) – energy. The relationship between the incoming and outgoing energy of the organization is established, which made it possible to generalize the concept of "efficiency" within the framework of the energy-entropy approach. Unlike classical efficiency, it is proposed that the entropy be considered an alternative measure of the "effective organization of the system". Based on this, the value of the organization’s resources is formed from two components – energy and entropy. In the framework of the energy-entropic concept of the organization and the energy turnover under consideration, the energy value of resources is defined as the ratio of the organization's incoming and outgoing energy over a certain period of time. In this interpretation, the energy value of the organization’s resources is a kind of analogue of efficiency. It has been established that the value of resources can be considered both integrally and separately for each type of resource. Also, the paper proposes indicators reflecting the entropy value of resources in monetary terms. Conclusions. In this study, the category "value of the resources of the organization" is considered in the framework of the energy-entropic concept of the organization. The model of energy circulation of the organization is formulated and the value of the organization is considered from the point of view of energy efficiency and energy entropy. A system of indicators has been developed that makes it possible to comprehensively evaluate the entropy value of each resource individually and their total value. A tool for analyzing the dynamics of energy entropy is also proposed, and a relative indicator of the dynamics of entropies is substantiated, which comprehensively assesses structural and qualitative changes in the organization and makes it possible to identify problems of an energy-organizational nature that need to be addressed.